Intrinsic Capacity Assessment by a Mobile Geriatric Team During the Covid-19 Pandemic - Angioni, Davide; Nicolay, Camille; Vandergheynst, Frédéric; Baré, Robin; Cesari, Matteo; De Breucker, Sandra (Frontiers in Medicine, 2021)
In the autumn of 2020, the second wave of COVID-19 pandemic hit Europe. In this context, because of the insufficient number of beds in geriatric COVID units, non-geriatric wards were confronted with a significant number of admissions of geriatric patients. In this perspective article, we describe the role of a mobile geriatric team in the framework of COVID-19 pandemic, and specifically how it assisted other specialists in the management of hospitalized geriatric patients by implementing a new approach: the systematic assessment and optimization of Intrinsic Capacity functions. For each patient, assessed by this consultative team, an individualized care plan, including an anticipated end-of-life decision-making process was established. Intensity of care was most often not stated by considering chronological age but rather the comorbidity burden, the frailty status and the patient’s wishes. Further studies are needed to determine if this mobile geriatric team approach was beneficial in terms of mortality, length of stay, or functional, psychological and cognitive outcomes in COVID-19 geriatric patients.